The Effect of Individual Characteristics, Resilient and Work Ability on Intention to Leave and Employee Performance at PT Clariant Adsorbent Indonesia, Gresik - Muhammad Husain; Siti Mujanah; Tri Andjarwati (Jurnal Ekonomi dan Bisnis Jagaditha, 2022)
This study aims to determine and analyze the effect of Individual Characteristics, Resilient and Workability on Intention to Leave and Employee Performance. This study uses quantitative methods. The population is 214 employees of PT Clariant Adsorbent Indonesia, Gresik. Sources of data in this study using primary data obtained directly from employee respondents with google form. Data analysis was carried out using the Partial Least Square (PLS) method using SmartPLS Version 3 software to validate with Convergent Validity, Average Variance Extracted (AVE), Discriminant Validity and perform reliability with Composite Reliability and Cronbach's Alpha. The research method uses an explanatory clause with a sample of 109 respondents. Collecting data using a questionnaire and analyzed using Smart PLS 3.0 to test the validity and reliability. The results showed that individual characteristics and work ability had a significant positive effect on exit intentions with path coefficients of 0.168 and 0.6979, while resilient had a positive but not significant effect with path coefficients of 0.0023. Individual characteristics and work ability have a positive but not significant effect on employee performance with path coefficients of 0.0092 and 0.0517. Intention to leave and resilient have a positive and significant effect on employee performance with path coefficient numbers 0.6019 and 0.2837. The results of this study can prove that individual characteristics, work ability and intention to leave are factors up and down the performance of employees so that a strategy is needed to improve employee performance in terms of quality, quantity, work duties and responsibilities.